Vagus nerve stimulation for drug‐resistant epilepsy: A European long‐term study up to 24 months in 347 children. Issue 10 (17th September 2014) - Orosz, Iren; McCormick, David; Zamponi, Nelia; Varadkar, Sophia; Feucht, Martha; Parain, Dominique; Griens, Roger; Vallée, Louis; Boon, Paul; Rittey, Christopher; Jayewardene, Amara K.; Bunker, Mark; et al.
Summary Objective To gain insight into the long‐term impact of vagus nerve stimulation (with VNS Therapy) in children with drug‐resistant epilepsy, we conducted the largest retrospective multicenter study to date over an extended follow‐up period of up to 24 months. Methods The primary objective was to assess change in seizure frequency of the predominant seizure type (defined as the most disabling seizure) following VNS device implantation. Treating physicians collected data from patient records from baseline to 6, 12, and 24 months of follow‐up. Results The analysis population included 347 children (aged 6 months to 17.9 years at the time of implant). At 6, 12, and 24 months after implantation, 32.5%, 37.6%, and 43.8%, respectively, of patients had ≥50% reduction in baseline seizure frequency of the predominant seizure type. The responder rate was higher in a subgroup of patients who had no change in antiepileptic drugs (AEDs) during the study. Favorable results were also evident for all secondary outcome measures including changes in seizure duration, ictal severity, postictal severity, quality of life, clinical global impression of improvement, and safety. Post hoc analyses demonstrated a statistically significant correlation between VNS total charge delivered per day and an increase in response rate. VNS Therapy is indicated as adjunctive therapy in children with focal, structural epilepsies, who for any reason are not good candidates for surgical treatment following the trial of two or more AEDs. Children with predominantly generalized seizures from genetic, structural epilepsies, like Dravet syndrome or Lennox‐Gastaut syndrome, could also benefit from VNS Therapy. Significance The results demonstrate that adjunctive VNS Therapy in children with drug‐resistant epilepsy reduces seizure frequency and is well tolerated over a 2‐year follow‐up period. No new safety issues were identified. A post hoc analysis revealed a dose–response correlation for VNS in patients with epilepsy.